Decoupling of epitaxial graphene via gold intercalation probed by dispersive Raman spectroscopy - Pillai, P. B.; DeSouza, M.; Narula, R.; Reich, S.; Wong, L. Y.; Batten, T.; Pokorny, J. (Journal of applied physics, 2015)
Signatures of a superlattice structure composed of a quasi periodic arrangement of atomic gold clusters below an epitaxied graphene (EG) layer are examined using dispersive Raman spectroscopy. The gold-graphene system exhibits a laser excitation energy dependant red shift of the 2D mode as compared to pristine epitaxial graphene. The phonon dispersions in both the systems are mapped using the experimentally observed Raman signatures and a third-nearest neighbour tight binding electronic band structure model. Our results reveal that the observed excitation dependent Raman red shift in gold EG primarily arise from the modifications of the phonon dispersion in gold-graphene and shows that the extent of decoupling of graphene from the underlying SiC substrate can be monitored from the dispersive nature of the Raman 2D modes. The intercalated gold atoms restore the phonon band structure of epitaxial graphene towards free standing graphene.